Statutory Interpretation by Case-Based Reasoning through Abductive Logic Programming - Satoh, Ken (Journal of advanced computational intelligence and intelligent informatics, 1997)
This paper presents a method for solving statutory interpretation problem in the legal domain by using abductive logic programming. To interpret a rule, we must make an interpretation for legal predicates and terms in the rule; this interpretation is subject to change according to context. In this paper, we solve this problem byomparing and contrasting cases such as the CABARET system. This is done by translating case-based reasoning into abductive logic programming so that similarity between cases with respect to every undefined proposition in the rule is regarded as a set of abducibles that can be changed according to context. Our method is sound and complete in the sense that every possible interpretation is computed exactly.